FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI CABAI RAWIT DI DESA RASAU JAYA TIGA KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Suharti, Nur; Suyatno, Adi; Parulian Hutajulu, Josua (Fakultas Pertanian Universitas Janabadra, 2025)
This study's objective is to analyze the factors influencing the income of cayenne pepper farming in Rasau Jaya Tiga Village, Rasau Jaya District, Kubu Raya Regency. The background highlights the importance of the horticultural sector, particularly cayenne pepper, which has high economic value but is vulnerable to significant price fluctuations, thereby affecting farmers’ income. The research employed a quantitative descriptive method with a census approach, involving 52 farmers as respondents. Questionnaires, interviews, and observations were used to gather primary data, while relevant institutions provided secondary data. Data analysis was conducted using the Cobb-Douglas Unit Output Price (UOP) function. The results showed that 74.50% of income variation was influenced by seed price, lime price, organic fertilizer price, NPK fertilizer price, fungicide price, insecticide price, and labor wages. Simultaneously, all variables had a positive and significant effect on income; however, partially, only lime price, NPK fertilizer price, and labor wages had significant effects. NPK fertilizer had a positive effect, while lime price and labor wages negatively affected income. In contrast, seed price, organic fertilizer price, fungicide price, and insecticide price had no significant effect. The study concludes that optimizing the use of NPK fertilizer and managing lime and labor costs are crucial to improving farmers’ income.